2022
DOI: 10.1101/2022.07.20.22277872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geographic and Temporal Patterns in Covid-19 Mortality by Race and Ethnicity in the United States from March 2020 to February 2022

Abstract: Prior research has established that American Indian, Alaska Native, Black, Hispanic, and Pacific Islander populations in the United States have experienced substantially higher mortality rates from Covid-19 compared to non-Hispanic white residents during the first year of the pandemic. What remains less clear is how mortality rates have changed for each of these racial/ethnic groups during 2021, given the increasing prevalence of vaccination. In particular, it is unknown how these changes in mortality have var… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…A prior study found that increases in Covid-19 mortality in nonmetro areas during the second year of the pandemic were largely driven by increases in mortality among non-Hispanic white populations. 31 In line with this, a survey from 2021 found that white, older individuals who identified as Republican were the most vaccine hesitant population in the U.S.. 32 Another factor that may be contributing to high rural excess mortality is insufficient rural health infrastructure related to funding gaps and workforce shortages. 33 This may have affected access to Covid-19 treatment, including oral antivirals and monoclonal antibody treatments.…”
Section: Discussionmentioning
confidence: 98%
“…A prior study found that increases in Covid-19 mortality in nonmetro areas during the second year of the pandemic were largely driven by increases in mortality among non-Hispanic white populations. 31 In line with this, a survey from 2021 found that white, older individuals who identified as Republican were the most vaccine hesitant population in the U.S.. 32 Another factor that may be contributing to high rural excess mortality is insufficient rural health infrastructure related to funding gaps and workforce shortages. 33 This may have affected access to Covid-19 treatment, including oral antivirals and monoclonal antibody treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings also contribute to a broader literature examining the relationship between economic conditions and health. This literature has highlighted the complex ways in which aggregate-level economic downturns and individual-level job losses may impact health (Ruhm 2000;2005;Sullivan and Von Wachter 2009;Ruhm 2015;Stevens et al 2015), and, conversely, how shocks to population health may impact the economy (Adda 2016;Barro et al 2020; mortality rates (Bassett et al 2020;Ford et al 2020); these gaps declined but were not eliminated during the pandemic's second year (Aschmann et al 2022;Lundberg et al 2022;Truman et al 2022). Minorities also experienced greater all-cause mortality during the pandemic's initial months (Alsan et al 2021;Miller et al 2021;Polyakova et al 2021), and these gaps persisted through the pandemic's first year (Cronin and Evans 2021;Ruhm 2022;Foster et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study in 2022 showed that although there are now higher vaccination rates among non-Hispanic Blacks and Hispanics, which have reduced mortality, there remains a high disparity in mortality between these ethnic groups and non-Hispanic Whites [ 57 ]. Despite these high vaccination rates, as many as 10% of adults are unvaccinated and if they have cancer can have a higher risk of mortality than a vaccinated cancer patient.…”
Section: Discussionmentioning
confidence: 99%